The Iran nuclear archive: impressions and implications. Issue 2 (23rd February 2021) - Arnold, Aaron; Bunn, Matthew; Chase, Caitlin; Miller, Steven E.; Mowatt-Larssen, Rolf; Tobey, William H.
ABSTRACT: A review of selected on Iran's nuclear weapons program seized by Israeli intelligence confirms that: senior Iranian officials had decided in the late 1990s to actually manufacture nuclear weapons and carry out an underground nuclear test; that Iran's program to do so made more technical progress than had previously been understood; and that Iran had help from quite a number of foreign scientists, including access to several foreign nuclear weapon designs. The archive also leaves open a wide range of questions, including what Iran's nuclear-weapons-related plans and activities have been in 17 years since 2003.